การสร้างแบบประเมินบ้านรักษ์นิเวศสำหรับภูมิภาคร้อนชื้น - จิตพัต ฉอเรืองวิวัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
Nowadays, there are building energy assessment methods in many countries, for example, BREEAM (UK), CASBEE (Japan) GREEN STAR (Australia) and LEED (USA). However, these indexes can not be applied directly to Thailand because of climatic differences. From the life cycle assessment theory, energy consumption of building can reach as high as 60 – 90 percent during its life span of 30 – 50 years. This research analysed the process of material production, design and operation for the development of building assessment method. The development process consisted of embodied energy analysis of building materials. Factors that influenced design and operation including external factor as micro-climate, building form, thermal transfer and infiltration, internal factors such as lighting and electrical loads, and air-condition efficient factor were also analyzed. Proposed energy assessment index of building consists of micro climate sub-index (oC) values of 5.25 (good), 12.81 (average) and 20.37 (bad); building form index values of 0.50 (good), 3.50 (average) and 6.50 (bad); thermal transfer index (W/m2• oC) values of 0.06 (good), 2.64 (average) and 5.22 (bad); infiltration index (W/m2) values of 12 (good), 36 (average) and 60 (bad); lighting index (W/m2) values of 6 (good), 12 (average) and 18 (bad); appliance index (W/m2) values of 1.89 (good), 15.90 (average) and 29.91 (bad); air condition index values of 0.23 (good), 0.44 (average) and 0.65 (bad). The energy assessment of building (kWh/m2/yr) can be categorized in different levels. The values lower than 55 is counted as the excellent level (A+), 55 – 112.50 as very good level (A), 112.50 – 170 as good level (B+), 170 – 227.50 as average level (B), 227.50 – 285 as lower than the average level (C+), 285– 342.50 as low level (C), 342.50 – 400 as very low level (D+), and the values higher than 400 as the lowest level (D). This building assessment covers all building influential factors that can be used both for old and new buildings. Furthermore, this building assessment also provides design guidelines for architects, engineers and other stakeholders to improve those physical and policy impact factors for buildings in this region.